The Role of Renewable, Non-renewable Energy Consumption and Technology Innovation in Testing Environmental Kuznets Curve in Malaysia - Saudi, Mohd Haizam Mohd; Sinaga, Obsatar; Jabarullah, Noor H. (International Journal of Energy Economics and Policy, 2018)
This current paper investigates the role of renewable energy, non-renewable energy and technology innovation in testing the Environmental Kuznets Curve in Malaysia by using the annual data over the time from 1980 to 2017. We applied the advance econometrics to serve the purpose of investigation and therefore used the Auto Regressive Distributed Lags bound testing approach for assessing the presence of long-run relationship between the variables. The results of ARDL bound testing approach confirm the valid long run relationship between renewable energy, non-renewable energy, technology innovation and economic growth with carbon dioxide emission in Malaysia. The empirical results indicate that renewable energy consumption and technology innovation have significant and negative impact on carbon dioxide emission whereas, the non-renewable energy consumption and economic growth have a significant and positive impact on carbon dioxide emission. Furthermore, results also confirm the existence of inverted U-Shape curve in Malaysia. Keywords: Sustainable energy, green technology, renewable energy, technological innovation, environmental Kuznets Curve, Malaysia. JEL Classifications: Q20, Q56, O31 DOI: https://doi.org/10.32479/ijeep.7295